Acute Limb Ischemia Caused by Dissection following Percutaneous Coronary Intervention Using Right Radial Approach - Haris Ahmed; Jonathan Brown; Brooke Walterscheid; Phebe Abraham; Junaid Alam; Nabeel Ahmad; Syed Arman Raza (Case Reports in Cardiology)
Iatrogenic aortic dissection is a rare but potentially fatal complication of percutaneous coronary intervention (PCI). Iatrogenic aortic dissection following PCI is rare with most cases reporting dissection originating within the coronary vessels with propagation into the ascending aorta. In this specific case, dissection was without coronary involvement, with dissection extending from the ascending aorta into the descending aorta and iliac vessels. Although PCI via radial approach is associated with fewer vascular complications than with femoral approach, significant adverse outcomes may still occur and require prompt intervention. This case highlights the highly atypical presentation of iatrogenic aortic dissection following cardiac catheterization presenting as acute limb ischemia. In such patients as with ours, immediate surgical intervention is necessary with overall poor prognosis.